2001
DOI: 10.1002/1096-9071(20000201)63:2<178::aid-jmv1013>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection does not increase allergen-induced type 2 cytokine production, yet increases airway hyperresponsiveness in mice

Abstract: Severe respiratory syncytial virus (RSV)-induced disease is associated with childhood asthma and atopy. We combined murine models of allergen-sensitization and RSV infection to explore the interaction of allergic and virus-induced airway inflammation and its impact on airway hyperresponsiveness (AHR). We found that RSV infection during ova-sensitization (OVA/RSV) increased and prolonged AHR compared to mice only RSV-infected (RSV) or ova-sensitized (OVA). AHR is known to be associated with an increase in Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 41 publications
4
50
2
Order By: Relevance
“…Further, RSV infection during the OVA challenge phase resulted in increased AHR, eosinophil numbers, and enhanced expression of IL-4 and IL-5 in the lung (24). By contrast, RSV infection with A2 strain induced AHR in mice with allergic airways disease without inducing Th2 cytokines, but rather through increased IL-17A levels (25,26). Finally, RSV infection after OVA challenge in the absence of adjuvant sensitization also increased AHR and induced high levels of IL-4 and IL-5 and the accumulation of eosinophils and neutrophils into the airways (20).…”
mentioning
confidence: 94%
“…Further, RSV infection during the OVA challenge phase resulted in increased AHR, eosinophil numbers, and enhanced expression of IL-4 and IL-5 in the lung (24). By contrast, RSV infection with A2 strain induced AHR in mice with allergic airways disease without inducing Th2 cytokines, but rather through increased IL-17A levels (25,26). Finally, RSV infection after OVA challenge in the absence of adjuvant sensitization also increased AHR and induced high levels of IL-4 and IL-5 and the accumulation of eosinophils and neutrophils into the airways (20).…”
mentioning
confidence: 94%
“…with OVA in alum and subsequently aerosolized with OVA on days 2 2 through 6 post RSV infection found no increase in lung IL-4, IL-5 or IL-13 mRNA expression despite greater airway hyperresponsiveness (Peebles et al, 2001). There is an explanation for both results.…”
Section: Mechanisms Of Rsv Induced Allergen Immunomodulationmentioning
confidence: 87%
“…Moreover, other reports have shown that allergens and environmental pollutant exposure can alter the outcome of RSV infection (Gurkan et al, 2000;Makela et al, 2003). In murine models, researchers have demonstrated increased airway hyperresponsiveness when allergen is administered before infection to achieve sensitization and then challenge exposure is performed during infection (Peebles et al, 2001). This phenomenon has been demonstrated not only in the mouse but also in bovine models of RSV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In autopsy lung tissues from fatal HRSV disease cases, epithelial damage and mechanical airway obstruction are implicated as key features of HRSV pathogenesis (Johnson et al, 2007;Welliver et al, 2007). Although laboratory animal models of HRSV pathogenesis have been widely used to determine pathogenic mechanisms of HRSV infection, the commonly used lab strains of HRSV do not cause airway epithelial cell desquamation, airway mucus production, or lung dysfunction in mice (Moore et al, 2009a;Peebles et al, 2001). However, some strains of HRSV (e.g.…”
Section: Introductionmentioning
confidence: 99%